1988
DOI: 10.2307/2403627
|View full text |Cite
|
Sign up to set email alerts
|

Seed Banks at Six Open and Afforested Heathland Sites in Southern Sweden

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. SUMMARY(1) Germinable seed banks in the soil were determined for six sites in southern Sweden: a grazed heathland, four first generation Picea abies plantations aged 30-73 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 17 publications
5
38
0
1
Order By: Relevance
“…This is in agreement with other studies which have shown that the seedbank of this species is highly persistent: >30 years under coniferous plantations (Hill and Stevens, 1981) and >73 years under Picea abies (Granströ m, 1988). High densities present in mineral soil under bracken deep in the stand at Ramsley Moor are in keeping with the relatively rapid invasion by bracken which this site has experienced.…”
Section:    supporting
confidence: 92%
“…This is in agreement with other studies which have shown that the seedbank of this species is highly persistent: >30 years under coniferous plantations (Hill and Stevens, 1981) and >73 years under Picea abies (Granströ m, 1988). High densities present in mineral soil under bracken deep in the stand at Ramsley Moor are in keeping with the relatively rapid invasion by bracken which this site has experienced.…”
Section:    supporting
confidence: 92%
“…It supports distinctive plant and faunal assemblages of international importance including numerous specialised invertebrates (Webb 1989;Stubbs and Fry 1991;Desender and Bosmans 1998;Gajdos and Toft 2000;Goulson et al 2005). Along with agricultural conversion, afforestation has been a major cause of heathland loss in Europe (Noirfalise and Vanesse 1976;Granstro¨m 1988;Farrell 1993). Habitat re-creation initiatives have included removing areas of coniferous forestry planted over heathland (e.g.…”
Section: Introductionmentioning
confidence: 88%
“…Various authors mentioned that birch seeds are mostly found in the humus or uppermost soil layers (Hill 1979, Granström 1988, Houle 1998, Sullivan & Ellison 2006. Houle (1998) concluded that less than 2 % of birch seed rain reaches the persistent seed bank.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…2). However, viable willow and poplar seeds were only derived from samples collected in March and April (Staaf et al 1987, Granström 1988, Bakker et al 1996a, Falinska 1999, Bekker et al 2000, Berger et al 2004, Dölle & Schmidt 2009). Samples taken near willow and European aspen seed trees in May and June contained no viable seeds of either genus (Falinska 1999, Decocq et al 2004 due to a rapid loss of germination ability after deposition on soil (Barsoum 2002).…”
Section: Soil Seed Banks Of Salix Spp and Populus Tremula Lmentioning
confidence: 99%